A comparison of consumer reviews on the sales of experience and search goods. (1st January 2013) - Wang, Bin
Online consumer ratings and reviews have become very popular among online retailers and are found to be influential in affecting the sales of experience goods. However, the effects of such ratings and reviews on the sales of search or quasi-experience goods remain unknown. Using data collected from Amazon.com, this research examines how the impacts of consumer ratings and reviews differ across product categories. The results suggest that the sales of experience goods such as books are affected by consumer ratings and reviews, but the sales of quasi-experience and search goods such as digital cameras and USB flash drives are not. In addition, as the price of an experience item increases, consumer ratings and reviews become more influential on sales. In this paper, theoretical and practical implications of the research results are discussed.